A Review of Some Aspects of the Low-Income Country Debt Sustainability Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The Bank-Fund Debt Sustainability Framework (DSF) is a standardized framework for analyzing debt-related vulnerabilities in low-income countries (LICs). It aims to help countries monitor their debt burden and take early preventive action, to provide guidance to creditors in ensuring their lending decisions are consistent with countries' development goals, and to improve the Bank and Fund's assessments and policy advice. The DSF was last reviewed in 2006, and a reconsideration of some aspects of the framework is timely.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet